An overview of passive techniques for heat transfer augmentation in microchannel heat sink - Sidik, N. A. C. (Elsevier Ltd, 2017)
Active and passive cooling are the two possible methods for removing heat. An active cooling system is the one that involves the use of energy as opposed to passive cooling that uses no energy. Passive cooling methods are cost effective and more reliable than active cooling due to the absence of moving parts. Microchannel heat sink is one of high-tech devices that have widely considered passive cooling methods especially for electronics cooling. In this paper, the use of passive cooling methods in microchannel heat sink is comprehensively discussed. This paper also present the effects of some important parameters such as the type of channel types, surface roughness, fluid additives, and Reynolds number on the rate of heat transfer in microchannel heat sink. Finally, the conclusions and important summaries were presented according to the data collected.